Mashya and Mashyana unearthed myth, metonymy and the unknowing subject - Dabashi, Hamid 1951- (Edinburgh University Press, 2024)
"What if all we see, read, feel, fear, desire and repress in contemporary film, fiction and poetry are metonymic substitutes for much older and more ancient mythologies? What if our modern mythologies are not actually that modern?0Using Iran as an example of an ancient civilization with a sustained course of continuity all the way to the present time, this book moves towards a philosophical reflection on the relationship between what we see and feel today when engaging with art, literature and film and what we have otherwise deeply buried in the forgotten layers of our collective consciousness from time immemorial.0This is the story of Mashya and Mashyana Unearthed, an exploration of when and where ancient myths become metonymic in varied forms of contemporary cultural and aesthetic representations."
Keywords: Mythology in motion pictures; Mythology, Iranian; Mythology, Iranian, in literature; Mythologie au cinéma; Mythologie iranienne